The Influence Of Liquidity And Profitability On Stock Prices Of Food And Beverage Companies Listed In Indonesia Stock Exchange - Ermelinda Suryanti Loya; Christina Heti Tri Rahmawati (Universitas Mercu Buana, 2022)
This study aims to determine if:1) liquidity and profitability simultaneously have a significant influence on stock prices of food and beverage companies listed in Indonesia Stock Exchange (IDX) for the 2015-2019 period, 2) liquidity partially has a significant influence on stock prices of food and beverage companies listed in IDX for the 2015-2019 period, 3) profitability partially has a significant influence on stock prices of food and beverage companies listed in IDX for the 2015-2019 period. The research population is 26 food and beverage companies listed in IDX for the 2015-2019 period. The research sample is 16 companies. The sampling technique used is purposive sampling. Data are obtained from the companies’ annual reports. The data analysis technique in this study is multiple linear regression analysis. The results of this study show that: 1) liquidity and profitability simultaneously have a significant influence on stock prices of food and beverage companies listed in IDX for the 2015-2019 period, 2) liquidity partially has no significant influence on stock prices of food and beverage companies listed in IDX for the 2015-2019 period, 3) partially profitability has a significant influence on stock prices of food and beverage companies listed in IDX for the 2015-2019 period.